DECISION SUPPORT SYSTEM FOR MOUNTAIN CLIMBING SELECTION IN INDONESIA USING THE MULTI-FACTOR EVALUATION PROCESS (MFEP) METHOD - Achmad Imam Dairobbi; Muhammad Fairuzabadi (CV. Fahr Publishing, 2025)
Mountain climbing is a popular activity among various groups; however, selecting a suitable mountain can be challenging for climbers. Several factors, such as trail difficulty, altitude, climbing duration, cost, and water availability, must be considered to ensure a safe and comfortable climb. Therefore, this study develops a web-based Decision Support System (DSS) to assist climbers in choosing a mountain that matches their preferences. This research employs the Multi-Factor Evaluation Process (MFEP) method to evaluate mountains based on predetermined criteria. The system assigns weights to each factor and calculates evaluation scores to generate the best mountain recommendations. The system is developed using PHP for the backend, MySQL for the database, and Bootstrap for a responsive user interface. The study results indicate that the system can provide objective and accurate mountain recommendations. System testing using the Black Box Testing method confirms that all features function as intended. Based on MFEP calculations, the system ranks mountains according to relevant factors, enabling climbers to make informed and safer decisions.